2022
DOI: 10.1002/dvg.23494
|View full text |Cite
|
Sign up to set email alerts
|

Advances in periodontal stem cells and the regulating niche: From in vitro to in vivo

Abstract: Summary Periodontium possesses stem cell populations for its self‐maintenance and regeneration, and has been proved to be an optimal stem cell source for tissue engineering. In vitro studies have shown that stem cells can be isolated from periodontal ligament, alveolar bone marrow and gingiva. In recent years, more studies have focused on identification of periodontal stem cells in vivo. Multiple genetic markers, including Gli1, Prx1, Axin2, αSMA, and LepR, were identified with the lineage tracing approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…While periodontal MSCs in an inflammatory environment were characterized in vitro (Wei et al 2018; Zheng et al 2019; Lei et al 2022), those studies could not replicate the in vivo conditions and the intricate communications with surrounding tissues (Yi et al 2022). The approach in this current study enabled identification of the distinct changes of the Gli1 + MSCs within the periodontium at various locations and time points in an induced periodontitis model.…”
Section: Discussionmentioning
confidence: 99%
“…While periodontal MSCs in an inflammatory environment were characterized in vitro (Wei et al 2018; Zheng et al 2019; Lei et al 2022), those studies could not replicate the in vivo conditions and the intricate communications with surrounding tissues (Yi et al 2022). The approach in this current study enabled identification of the distinct changes of the Gli1 + MSCs within the periodontium at various locations and time points in an induced periodontitis model.…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium between the pro-inflammatory response and the stemness of PDLSCs is a key factor in determining whether tissue integrity and homeostasis is maintained or if disease progression occurs (Zhao et al, 2022). It has been observed that long-term stimulation of PDLSCs by P. gingivalis lipo-polysaccharide (LPS) resulted in an increase in cellular cytokine production and LPS also prevents the development of osteoblasts by impairing ALP activity and mineral synthesis in PDLSCs (Chen et al, 2021;Xu et al, 2023).…”
Section: Periodontal Ligament Stem Cells (Pdlscs)mentioning
confidence: 99%
“…With the advent of stem cell isolation techniques, it was later seen that not only fully differentiated PDL cells but also these stem cells residing in the periodontal ligament, took part in regeneration (Costela-Ruiz et al, 2022). As it is known that regeneration involves the Melcher's triad, the cells and in particular, the stem cells become an indispensable tool to achieve optimal regeneration (Ward, 2022;Yi et al, 2022). To expedite the regenerative potential of these stem cells, various light sources including LASERs and LEDs have been proven to be beneficial in the stimulation of the PDLSCs as mentioned in Table 1.…”
Section: Effect Of Laser On Pdlscsmentioning
confidence: 99%
See 1 more Smart Citation